THE INFLUENCE OF DIGITAL COMPETENCE AND WORK FACILITIES ON THE PERFORMANCE OF STATE CIVIL APPARATUS IN THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY (BPKAD) SERDANG BEDAGAI REGENCY - Wilda Tilawatil Aulya Purba; Satria Tirtayasa (PT. Radja Intercontinental Publishing, 2026)
The purpose of this study is to analyze and test the extent to which digital competence and work facilities influence the performance of civil servant employees at the Regional Financial and Asset Management Agency (BPKAD) of Serdang Bedagai Regency. This study uses a quantitative method approach using Multiple Linear Regression analysis on IBM SPSS Statistics 25 software. The population in this study were all ASN employees at the Regional Financial and Asset Management Agency (BPKAD) of Serdang Bedagai Regency, totaling 53 people. The data source in this study comes from primary data, namely from the results of questionnaires/surveys filled out directly by respondents. The results of this study indicate that digital competence has a positive and significant influence on the performance of civil servant employees at the Regional Financial and Asset Management Agency (BPKAD) of Serdang Bedagai Regency. Meanwhile, work facilities do not have a significant influence on the performance of civil servant employees at the Regional Financial and Asset Management Agency (BPKAD) of Serdang Bedagai Regency. Based on the results of the Simultaneous test (f count), it shows that digital competence and work facilities together have a significant effect on employee performance. ASN of the Regional Financial and Asset Management Agency (BPKAD) of Serdang Bedagai Regency..